CRANIAL OSTEOLOGY COMPARED TO CARACARA CHERIWAY (JACQUIN, 1784) AND CARACARA PLANCUS (MILLER, 1777) (AVES: FALCONIDAE) - Guzzi, Anderson (2015)
http://dx.doi.org/10.5902/2179460X14839The Caracara genus (Aves: Falconidae) is composed by species C. cheriway, (“Crested Caracara”), and C. plancus (Southern Caracara). This study aimed to describe in detail and compared the cranial osteology of C. cheriway and C. plancus, identifying osteological cranial characters for a future systematic work. The two common characters of Caracara species are: the projection of rostro parasphenoid reaches 50% of the distance from the occipital condyle to the pterygoid; the upper maxilla has about 4/9 of the total length of theskull, the symphysial portion of mandible occupies about 1/7 of its total length, the proximal portion of lacrimal bone ends in a rounded shape and has about 1/4 of the width of the distal portion. The unique characters of C. cheriway are: the interorbital width is about 1/2 of the parietal region, shows a frontal bone prominence; presence of lacrimal process of frontal bone; the proximal portion of the lacrimal bone reaches 1/5 of the distance from the orbital arc to the jugal bone; the distance between the distal portions of two lacrimal bones reach 5/6 of the parietal width, the ratio between the interorbital diameter and parietal region ranges from 2 times; the zygomatic process occupies about 40% of the distance between its origin in the skull and jugal bone. The unique characters of C. plancus are: the interorbital width is approximately 4/7 of the parietal width; show a rostral medial concavity; the proximal portion of the lacrimal bone is about 1/4 of the width of the distal; the proximal portion of the lacrimal bone reaches 1/7 of the distance from the orbital arc to the jugal bone; the distance between the distal portions of two lacrimal bones reaches 6/7 of the width parietal one; the ratio between the interorbital diameter and parietal region varies 1, 75 times, the zygomatic process occupies about 35% of the distance between its origin in the skull and jugal bone.